The effect of auditory-visual stimuli in the Lithuanian non-word repetition test - Krivickaitė-Leišienė, Eglė (Taikomoji kalbotyra, 2023)
The aim of this study is to compare research data collected using two different non-word repetition test procedures (live stimuli vs. audio-recorded stimuli). The study sample consists of 100 typically developing children (aged 4;00–5;11) and 50 adults (mean age ~ 30).The comparison of the different modes of the non-word repetition test suggests that the presentation of the stimuli (live vs. audio-recorded) influences the accuracy of the test results. The study found that visual stimuli significantly improved non-word repetition accuracy for both children and adults compared to audio-recorded stimuli (F(1.98) = 8.250, p < 0.005) and (F(1.43) = 8.927, p < 0.005), respectively. It was expected that visual stimuli would have a greater effect on adults than on children, but this hypothesis was not supported by the results.
Keywords: Non-word repetition test; language perception; language acquisition; auditory-visual stimuli